Analysis of a Bacillus subtilis Proteinase Mutant - Shoer, Ruth (1972)
A Bacillus subtilis mutant having a phenotype manifesting reduced extracellular proteolytic activity was investigated. An extracellular protein was isolated and shown by fingerprint analysis to be a fragment of the wild-type enzyme. By using previously established molecular weights for the wild-type enzyme (2.9 × 10(4)) and the two polypeptide chains derived from it (1.4 × 10(4) each), with the amino acid analysis and fingerprints of both wild-type and mutant proteins, a molecular weight of 1.57 × 10(4) was assigned to the mutant protein. (32)P-diisopropylphosphate labeling of the mutant protein showed only 1 in 53 molecules to be functional. Thin-layer chromatography on Sephadex G-75 demonstrated that the active molecules were separable from the bulk of the isolated protein and had the same mobility as the wild-type enzyme. Fingerprints of tryptic digests of (32)P-diisopropylphosphate-labeled wild-type and mutant proteins showed that the labeled peptides had identical characteristics.